Alteration in lipid composition of plasma membranes of sensitive and resistant Guerin carcinoma cells due to the action of free and liposomal form of cisplatin - Naleskina, L.A.; Todor, I.N.; Nosko, M.M.; Lukianova, N.Yu.; Pivnyuk, V.M.; Chekhun, V.F. (Experimental Oncology, 2013)
Aim: To study in vivo changes of lipid composition of plasma membranes of sensitive and resistant to cisplatin Guerin carcinoma cells under influence of free and liposomal cisplatin forms. Materials and Methods: The isolation of plasma membranes from parental (sensitive) and resistant to cisplatin Guerin carcinoma cells was by differential ultracentrifugation in sucrose density gradient. Lipids were detected by method of thin-layer chromatography. Results: It was determined that more effective action of cisplatin liposomal form on resistant cells is associated with essential abnormalities of conformation of plasma membrane due to change of lipid components and architectonics of rafts. It results in the increase of membrane fluidity. Conclusion: Reconstructions in lipid composition of plasma membranes of cisplatin-resistant Guerin carcinoma cells provide more intensive delivery of drug into the cells, increase of its concentration and more effective interaction with cellular structural elements.